2018
DOI: 10.1111/jsap.12945
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma of the ulnar nerve in the carpal canal in a dog: treatment by marginal neurectomy

Abstract: Peripheral nerve sheath tumours arising in the plexus or peripheral nerves can be treated by limb amputation. There are few reports of these tumours affecting peripheral nerves in the distal regions of the limbs. Here we describe a case of neurofibroma affecting the palmar branch of the ulnar nerve in an Irish setter. Surgical treatment in the region of the carpus by ulnar neurectomy resulted in resolution of chronic thoracic limb lameness. At 11 months following the surgery, clinical examination and MRI did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Based on the location of the tumors, taking into account their distance from the components of the nervous system, NSTs may belong to the root group, which involves nerves adjacent to the brainstem or spinal cord; the plexus group, which involves the brachial or lumbosacral plexus; or the peripheral group, which includes tumors arising distal to the brachial or lumbosacral plexus [ 5 ]. The most common locations of NSTs in dogs are the roots of the spinal nerves, especially at the level of the cervicothoracic spinal segment and in the brachial plexus and, occasionally, cranial nerves [ 1 , 6 ] and the skin [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the location of the tumors, taking into account their distance from the components of the nervous system, NSTs may belong to the root group, which involves nerves adjacent to the brainstem or spinal cord; the plexus group, which involves the brachial or lumbosacral plexus; or the peripheral group, which includes tumors arising distal to the brachial or lumbosacral plexus [ 5 ]. The most common locations of NSTs in dogs are the roots of the spinal nerves, especially at the level of the cervicothoracic spinal segment and in the brachial plexus and, occasionally, cranial nerves [ 1 , 6 ] and the skin [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arthrography adds to the capabilities of conventional CT and MRI by distending the joint capsule, identifying contrast solution leakages and ligament tears of the human wrist. Although previous studies have shown that MRI is a feasible imaging modality, not only for research but also for clinical use in case of carpal pathology in dogs, to the best of the authors' knowledge, no articles have reported the use of CTA and high‐field 3 Tesla MRA in the evaluation of the carpal ligaments of the dog. The objective of this study was (1) to determine whether the addition of intra‐articular contrast medium increases the visualization of normal canine carpal ligaments compared with conventional CT and MRI techniques, (2) to determine which imaging technique offers the best visualization of the ligaments overall, and (3) to determine the interobserver agreement.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described surgical excision of the tumour alongside thoracic limb amputation is the treatment of choice for PNSTs 1,2 . Compartmental resection with preservation of the limb has also been described, with previous case reports of neurectomies having good results when performed on benign PNSTs, with good limb function reported postoperatively 12,22 . This was discussed with the owner but declined due to an increased risk of recurrence or likelihood of not achieving clean margins and also the impact of resection of the median nerve on limb function.…”
Section: Discussionmentioning
confidence: 95%
“…1,2 Compartmental resection with preservation of the limb has also been described, with previous case reports of neurectomies having good results when performed on benign PNSTs, with good limb function reported postoperatively. 12,22 This was discussed with the owner but declined due to an increased risk of recurrence or likelihood of not achieving clean margins and also the impact of resection of the median nerve on limb function. Histopathology of the original biopsy found the tumour to be a mildly invasive, unencapsulated neoplasm.…”
Section: Discussionmentioning
confidence: 99%